NETWORK APPROACH TO ANALYSIS OF QUANTITATIVE TRAIT LOCI FOR TUMOR NECROSIS FACTOR (TNFα-863, TNFα-308, TNFα-238), VASCULAR ENDOTHELIAL GROWTH FACTOR (VEGF-2578, VEGF+936) AND MATRIX METALLOPROTEINASE (ММР2-1306, ММР3-1171, ММР9-1569) GENES IN AGERELATED MACULAR DEGENERATION - A. V. Shevchenko (SPb RAACI, 2017)
Age-related macular degeneration is one of the most widespread multifactorial eye diseases. Polymorphic functional alleles of vascular endothelial growth factor (VEGF) combined with matrix metalloproteinase (MMP) gene and tumor necrosis factor (TNF) gene variants may influence the development of disease. We have performed frequency analysis of their polymorphisms in regulatory regions of VEGF (rs 699947, rs 3025039), ММР2 (rs 2438650), ММР3 (rs 3025058), ММР9 (rs 3918242), TNFα (rs1800630, rs1800629, rs 361525) genes, and their combinations in a group of patients with age-related macular degeneration (MD). Frequencies of TNFα (rs1800629) genotypes significantly differed for the MD patients and control group. Upon the combined genotype analysis, we have revealed six constellations of VEGF-ММР genes that were positively associated with the disease development. Five of them included minor homozygous genotype VEGF-2578АА. A combined analysis of VEGF – TNFα genes polymorphisms has shown presence of both positive and negative complex genotypes. The most significant differences have been detected by comparative analysis of the complex genotypes frequencies which included 8 polymorphic regulatory gene regions of all genes studied. In most genetic complexes associated with the disease development, homozygous TNFα-863СС, homozygous MMP2-1306 ТТ, and MMP9-1562СС genotypes have been detected, together with the combination of homozygous VEGFA+936СС genotype in the same patients. We can assume that harboring allelic variants, which may contribute to angiogenesis prorcesses is typical for the genome of patients with macular degeneration, along with low-level production of pro-inflammatory regulatory factors and enzymes participating in degradation of extracellular matrix. Analysis of complex genetic factors, procing some factors taking part at the pathological process being the regulators of production for each other, is more informative when detecting protective and resistant markers of the disease development rather than single genetic markers, thus being useful for genomic screening.